2005
DOI: 10.1017/s0022112005003782
|View full text |Cite
|
Sign up to set email alerts
|

Translating circular thrust bearings

Abstract: Thrust bearings have been the object of a considerable amount of research for many years. The attention that these bearings have received is primarily due to the important role they play in the design and operation of heavy equipment. The objectives of this work are to examine the effect of translation and bearing geometry, such as recess depth and width, on the performance of circular thrust bearings. A closed-form solution is obtained for laminar viscous flow that extends prior results which generally focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Manring [22], where Reynolds equation of lubrication was integrated considering the effect of tangential velocity.…”
mentioning
confidence: 99%
“…Manring [22], where Reynolds equation of lubrication was integrated considering the effect of tangential velocity.…”
mentioning
confidence: 99%
“…The mean fluid thickness and PD for invariable and dynamic operating conditions were experimentally quantified and compared. Furthermore, under the assumptions that the space between the slipper and swash plate is fixed and that the slipper is nontilted and straight, Johnson and Manring [4] developed an analytic model based on classical lubrication theory, which also considers tangential speed. They observed that an increase in slipper pocket depth reduces friction.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the work has focused on analysing the forces and torques over the slipper experimentally and analytically . The effects of slipper spin, tangential velocity, tilt, slipper non‐flatness, inlet orifice and conditions for metal to metal contact, among others, are investigated . Canbulut et al .…”
Section: Introductionmentioning
confidence: 99%